Beneficial Impact of bFGF Antisense Therapy in a Rat Model of Pulmonary Fibrosis - Chen, Zhenshun; Tan, Weijun; Zhang, Li; Tan, Qiuyue; Yang, Jiong (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2015)
Objectives: This study aims to explore basic fibroblast growth factor (bFGF)’s role in the development of pulmonary fibrosis through applying bFGF antisense oligonucleotide therapy in a rat model of pulmonary fibrosis. Methods: Thirty rats were randomly divided into five groups: bFGF sense-transfected, bFGF antisense-transfected, null vector-transfected, pulmonary fibrosis (PF), and control groups. Sense, antisense, null, and PF groups were administered bleomycin to induce pulmonary fibrosis. Sense, antisense, and null vectors were intratracheally injected into the lungs of their respective groups followed by sacrifice after 28 days post-injection. Lung coefficients, H&E and Masson trichome staining, and serum and bronchoalveolar lavage fluid bFGF expression were comparatively assessed in addition to lung homogenate mRNA expressions of several select proteins and hydroxyproline content. Results: The antisense and sense groups had significantly decreased and increased lung coefficients and pulmonary fibrosis than the PF and null groups, respectively, with the pulmonary fibrosis stage positively correlated with treatment. Antisense, PF, and null groups showed significantly reduced collagen fiber levels compared to the sense group. The antisense group displayed significantly lower serum and lavage fluid bFGF expression in addition to significantly lower bFGF, α-smooth muscle actin, Smad3, transforming growth factor-β1, connective tissue growth factor, collagen I (and significantly higher Smad7) mRNA expression relative to the PF and null groups. The antisense and sense groups showed significantly higher hydroxyproline content relative to the PF and null groups. Conclusions: bFGF appears to promote collagen I synthesis and upregulates TGF-β1/Smad signaling to promote lung fibroblast proliferation and differentiation in pulmonary fibrosis. bFGF antisense oligonucleotide therapy shows promise in preventing the development of pulmonary fibrosis, likely though a TGF-β1/Smad-based signaling mechanism.